Peran Aksesibilitas dan Pengalaman Dalam Niat Berkunjung Kembali di Siola Surabaya - Nur Rochma Isnaini; Devi Aprillia Putri; Mila Hariani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to examine the role of accessibility and visitor experience on intentions to return to Siola Surabaya. Siola, as one of the iconic shopping and cultural centers in Surabaya, always tries to increase its attractiveness through various infrastructure and service improvements. The research results show that good accessibility and positive experiences significantly influence revisit intentions.